2011
DOI: 10.1097/ta.0b013e3181d40418
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Locking Plate Fixation With Minimally Invasive Plate Osteosynthesis in a Subtrochanteric Fracture Model

Abstract: The LCP-DF construct proved stronger than the DCS in terms of ultimate strength by biomechanical testing of a simulated subtrochanteric femur fracture with comminution. Although the nail construct proved strongest, the biomechanical performance of the locking plate construct may lend credence to the use of a locking plate versus the DCS plate for minimally invasive plate osteosynthesis of subtrochanteric femur fractures, which may be technically difficult to fix using a nail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…The strength of LCP‐DF 1 was previously demonstrated in a biomechanical study that showed that its axial stiffness was greater than that of a dynamic condylar screw (DCS) plate (Kim et al . ). The main advantage of the LCP‐DF 1 is that short terminal fragments are more easily fixed because up to 7 screws can be inserted, similar to the stainless steel cobra head plate (Kirker‐Head and Fackelmann ).…”
Section: Discussionmentioning
confidence: 97%
“…The strength of LCP‐DF 1 was previously demonstrated in a biomechanical study that showed that its axial stiffness was greater than that of a dynamic condylar screw (DCS) plate (Kim et al . ). The main advantage of the LCP‐DF 1 is that short terminal fragments are more easily fixed because up to 7 screws can be inserted, similar to the stainless steel cobra head plate (Kirker‐Head and Fackelmann ).…”
Section: Discussionmentioning
confidence: 97%
“…Biomechanical studies have shown locking plates to achieve stronger and stiffer fixation than other angularly stable implants. [3][4][5] Clinical data on the use of locking plates in proximal femur fractures are however limited to only 2 case series. 6,7 These studies have raised concern regarding proximal femur locking plates having higher than expected failure rates, even in the hands of well-trained and experienced surgeons.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous biomechanical comparison study of intramedullary devices and extramedullary devices, Zlowodzki et al 23 reported that the fixation strength of LISS was 13% greater for axial loading and 45% weaker for torsional loading compared with intramedullary nailing. However, Kim et al 24 suggested that the fixation strength of LCP-DF was 250% weaker for axial loading and similar for ultimate displacement compared with PFN. These studies implied that PFNA allow patients to bear partial weight at an earlier stage not only because it can sustain a large axial load but because it can also enhance its bone purchase by compacting cancellous bone with a helical blade.…”
Section: Discussionmentioning
confidence: 99%